"Il y a toujours l'Autre": Towards a Photomosaic Reading of Otherness in Island Short Story Collections. Issue 1 (April 2018) - André, Bénédicte
Abstract : Drawing on the works of spatial theorist Edward Soja and photomontage artist Robert Silvers, this article will discuss the creative and rallying power of otherness by examining relational tensions between "the one" and "the many" in visual and textual productions about and from islands. Without reducing islands' multifaceted diversity to a fixed set of universal characteristics, I argue that the art of contrast undergirding the technique used in Silvers' Photomosaics can be applied to the analysis of short stories by contemporary New Caledonian writer Claudine Jacques through what I call a photomosaic reading. Just as physical islands summon up the binary of fragment and whole in their relation to the mainland, individual photographs and short stories will be envisaged as metaphorical islands that evoke and challenge notions of limit, brevity, and presence while bringing forth a distinctive aesthetics of contrast.